Estudo da degomagem e clarificação de óleo bruto do farelo de arroz (Oryza sativa) visando refino físico - Lüdtke, Fernanda Luisa (2016)
The rice is one of the cereals most consumed in world, consumption carried out mostly in the form of grains whose processing generates by-products such a rice bran, from which is obtained the rice bran oil. Due the presence of phospholipids, gums, waxes, this oil has a darker color and higher viscosity as compared to other vegetable oils. Also contains γ-orizanol, composed absent in other oils, which have been assigned antioxidants and hypocholesterolemics effects; but to become fit for consumed, the rice bran oil needs to be refined. The refining method modifies the oil composition; the chemical refining cause significant losses or changes in composition of rice bran oil; in the physical refining loss of these components is minimized, however the rice bran oil must have a phosphorus content below to 10 mg.kg-1 before to desodorization step, for to perform the physical refining. Thus, the aim of this study was to conduct studies on the degumming in order to make it fit the physical refining; and on the clarification, so that besides fit the physical refining, this is attractive to the consumer. Clarifying activity tests were performed two clarifiers lands: Tonsil ® Supreme 180 FF Tonsil ® and Actisil FF 280 added in different proportions (1.0, 1.5 and 2.0); degumming with water (0.6 and 5%) and phosphoric acid (0.2%), citric (0.5%); and clarification tests using the land and proportions that showed the best clarifying activity. There was the physicochemical characterization of crude, degummed oil and clarified oil with 2% of the earth Tonsil ® Supreme 180 FF and profile of fatty acids, γ-oryzanol content, tocopherols and tocotrienols content. The clarifier earth Tonsil ® Supreme 180 FF was the one with the best clarifying activity in the proportion of 2%, and when added at the rate of 1.5% showed the same activity clarifying that the earth Tonsil ® Actisil 280 FF added at a ratio of 2 0%; which was verified both in the clarifier activity tests, for the clarification test. The degumming with 5% water caused a reduction of the phosphorus content to less than 10 mg.kg-1. Thus, the degumming with 5% water, followed by clarification test using citric acid (50%) in the proportion of 0.5% to 2.0% addition of the clarifier earth Tonsil ® Supreme 180 FF, to provide a suitable oil physical refining, and the physical and chemical characteristics similar to crude oil and within the requirements specified by law.